Mycobacterium intracellulare subsp. chimaera from Cardio Surgery Heating-Cooling Units and from Clinical Samples in Israel Are Genetically Unrelated - Mor Rubinstein (MDPI AG, 2021)
Non-tuberculous mycobacteria (NTM) are opportunistic pathogens that cause illness primarily in the elderly, in the immunocompromised or in patients with underlying lung disease. Since 2013, a global outbreak of NTM infection related to heater-cooler units (HCU) used in cardio-thoracic surgery has been identified. This outbreak was caused by a single strain of Mycobacterium intracellulare subsp. chimaera. In order to estimate the prevalence of this outbreak strain in Israel, we sampled Mycobacterium intracellulare subsp. chimaera from several HCU machines in Israel, as well as from patients, sequenced their genomes and compared them to the outbreak strain. The presence of mixed mycobacteria species in the samples complicated the analysis of obtained sequences. By applying a metagenomic binning strategy, we were able to obtain, and characterize, genomes of single strains from the mixed samples. Mycobacterium intracellulare subsp. chimaera strains were compared to each other and to previously reported genomes from other countries. The strain causing the outbreak related to the HCU machines was identified in several such machines in Israel but not in any clinical sample.